Modern Approaches of Improvement the Investment Attractiveness of the Region (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article analyzes the investment climate and investment dynamics of the regions. The main problems that hinder investment in the regionʼs economy are found. Priorities and innovative forms enhance the investment attractiveness of the region are defined. Innovative forms of strengthening investment activity in the region under the conditions of European integration are proposed. Ukraine has necessity to develop and implement modern approaches in oder to stimulate investment in the region. For the practical improvement of investment attractiveness of the region we proposed such forms of stimulating investment in the region as: clustering; competitor management; territorial marketing; branding area.
Keywords: investment climate; investment attractiveness; clustering; competitor management; territorial marketing; branding area